Finite Element Analysis of Stress Distribution in AL6061 Frame Structures under Varying Applied Loads - Sabtu, Muhammad Amin; Admi, Aidid Ezmi; Mohamed Salleh, Muhammad; Osman, Saliza Azlina; Osman, Shahrul Azmir (International Journal of Integrated Engineering, 2024)
The demand for lightweight and high-performance structures has driven the popularity of commercially available aluminum alloys such as AL6061, particularly in the semiconductor industry. However, predicting stress distribution accurately within AL6061 frame structures under diverse loading conditions remains a significant challenge for clients due to the complex nature of their behavior. To address this challenge, a study has been conducted that utilizes the advanced 3D simulation software SolidWorks 2023 to model frame structures and evaluate their behavior under varied loads of up to 150% of the structure's weight, which is a significant departure from the standard loading conditions. The goal is to provide clients with a comprehensive and realistic understanding of the performance of their frame structure. The study evaluates the designed frame structure's stress, strain, displacement, and safety factors, ensuring that all values fall within the acceptable range. This gives clients a detailed understanding of how their structures will perform under various loading conditions. Material properties of the aluminum alloy, including its elastic modulus and yield strength, were also considered in the analysis. This in-depth analysis provides clients valuable insights into designing and optimizing lightweight and high-performing frame structures in the semiconductor industry, enabling them to make informed decisions about their structures.